Carthage and Alexander. The troublesome tracing of relationships - San José Campos, Christian (Antiguo Oriente, 2021)
The aim of this paper is to analyze the bond of Carthage with the figure of Alexander the Great. In order to accomplish it, this study tracks the scarce but important information preserved in classic sources in order to analyze them and contextualize their data. The study will mainly focus on the following scenarios: the siege of Tyre in 332 BC, the alleged Carthaginian espionage on Alexander’s ranks and the diplomatic parish received by the Macedonian in 323 BC in Babylon. Moreover, it will also briefly address the Hypomnemata and the Last Plans. Finally, concise conclusions are drawn that refute Alexander’s traditional hostile thinking and anti- Carthaginian approach.